Social Role Conceptions and CSR Policy Success - Gössling, Tobias (Journal of business ethics, 2007)
Businesses are eager to present themselves as honest and reliable corporate citizens who care about the overall well-being of society. This article researches whether different role conceptions of businesses regarding social issues are related to their success in dealing with social demands. Do socially active companies have a better social reputation than inactive companies? This relationship is determined by first extracting the social role conceptions of the companies from their Corporate Social Responsibility reports and then comparing this data to their social reputations. The analysis shows that there is indeed a relationship between these two variables. Companies with a broad social role conception score significantly better on their social reputations than companies with a narrow role conception. Social role conceptions therefore matter when dealing with social demands.